Utilizing Game Online to Enhance University Student’s Speaking Skill - Wildona Zumam; Rikzen Alfarozi (Jurnal Pendidikan Edutama, 2022)
Abstract: Speaking is complex skill that express the ideas, opinions, desires, our feelings freely, structured and spontaneously that aim give or get information and knowledge from other people. The speaking process base on experiences that can be obtained through discussion, reading, observation, and listening. All the students want to speak English fluently; therefore students must learn to boost their speaking skills. Talking about speaking boosting, the boosting is divided into several aspects ranging from boosting pronunciation, comprehension, grammar, and vocabulary. It can be used as a measurement our speaking is good or not. Almost all students have method to boosting English speaking skill namely online game. The students was familiar with gadgets rarely have online games, not only one but more online games on one gadget. This researcher have research the student of English department in academic year 2017-2020 with using interview method. The result of the study is can boost speaking skill but not effective to be Media learning in English program students Madura University. Abstrak: Berbicara adalah keterampilan kompleks yang mengungkapkan gagasan, pendapat, keinginan, perasaan kita secara bebas, terstruktur dan spontan yang bertujuan memberi atau mendapatkan informasi dan pengetahuan dari orang lain. Proses berbicara didasarkan pada pengalaman yang dapat diperoleh melalui diskusi, membaca, observasi, dan mendengarkan. Semua siswa ingin berbicara bahasa Inggris dengan lancar; oleh karena itu siswa harus belajar untuk meningkatkan keterampilan berbicara mereka. Berbicara tentang peningkatan berbicara, peningkatan dibagi menjadi beberapa aspek mulai dari peningkatan pengucapan, pemahaman, tata bahasa, dan kosa kata. Hal ini dapat digunakan sebagai ukuran baik atau tidaknya berbicara kita. Hampir semua siswa memiliki metode untuk meningkatkan keterampilan berbicara bahasa Inggris yaitu game online. Siswa yang akrab dengan gadget jarang memiliki game online, tidak hanya satu game online tetapi lebih pada satu gadget. Peneliti ini melakukan penelitian terhadap mahasiswa jurusan Bahasa Inggris tahun ajaran 2017-2020 dengan menggunakan metode wawancara. Hasil penelitian dapat meningkatkan keterampilan berbicara tetapi tidak efektif menjadi media pembelajaran pada mahasiswa program studi Bahasa Inggris Universitas Madura.